Low-cost water-in-salt electrolytes for electrochemical energy storage applications: a short review - Sakita, Alan Massayuki Perdizio; Noce, Rodrigo Della (Eclética Química, 2022)
The utilization of aqueous electrolytes is an emerging field in batteries and supercapacitors to overcome the safety concerns about the flammability of the typical organic electrolytes employed in these devices. Yet, aqueous diluted electrolytes limit the electrochemical stability window (ESW) restricting the device cell voltage. Surprisingly, the use of water-in-salt electrolytes (WISEs) has demonstrated the capability of suppressing the free water content of solution leading to an ESW expansion. On the other hand, since the first report of WISEs, most of these electrolytes have employed expensive salts for their preparation, hindering the replacement of the current electrolytes, utilized in energy storage devices, by WISEs. On the other hand, in recent years, the employment of low-cost salts for WISEs has been investigated as a strategy to circumvent these economic issues revealing to be feasible for widening the cell voltage. Herein, we summarize the recent progress and developments of WISEs produced with low-cost salts providing the challenges and perspectives toward their application in electrochemical energy storage.